(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Walking is the most underused form of travel. It appears to be less important in terms of safety because it only have a very small fraction of the overall right of way to move, access, or stroll. There are extremely few or no design considerations for pedestrians on the majority of Pune’s streets because pedestrians are few in numbers. This study’s objective is to assess Pune’s commercial street’s walkability. In order to conduct this study, one of the crowded streets in Pune’s city centre was chosen. A mixed method approach will be used to collect both qualitative and quantitative data. A visual survey and a pedestrian survey on a chosen street will be used to collect the data. Data about pedestrian infrastructure is gathered visually. Authors attempted to identify challenges faced by pedestrians during walking. Literature from books, newspapers, study papers, and maps is considered secondary data. The results of this study show how important it is to understand the pedestrian infrastructure in order to enable walkability on commercial streets in Pune’s city centre. The promotion of walking among the general public and walkability studies will help to accomplish desired outcomes. Finally, the paper concluded in finding walkability index of Laxmi road.